2017
DOI: 10.17219/acem/62454
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of combined radiochemotherapy in cervical cancer patients

Abstract: Background. Radiochemotherapy in cervical cancer was implemented to clinical practice based on 5 randomized clinical trials, published at the end of the 20 th century, which showed improvement in the total and symptomless survivals by about 10-18%. The increase of therapeutic index of such treatment can take place only when the efficiency of the treatment outweighs the increase of its toxicity. Thus, it is necessary to monitor treatment reaction during radiochemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Frecuently diarrhea (56% in the INC group vs. 51.6%) was found by Izmajłowicz et al. Regarding lifestyle, risk factors such as smoking, should be addressed with re-relevance, since smoking has a RR of 2.4 (95% CI: 1.7, 3.4) and the risk remains even with smoking cessation ( RR = 1.6, 95% CI: 1.0–2.7 ) ( 60 ). The risk increases in women who smoked for a period of 16 years (OR: 3.23, 95% CI: 1.33, 7.69), and continue in recurrent smokers who consume more than 20 cigarettes a day ( OR: 2.57, 95% CI: 1.49 to 4.45 ) ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frecuently diarrhea (56% in the INC group vs. 51.6%) was found by Izmajłowicz et al. Regarding lifestyle, risk factors such as smoking, should be addressed with re-relevance, since smoking has a RR of 2.4 (95% CI: 1.7, 3.4) and the risk remains even with smoking cessation ( RR = 1.6, 95% CI: 1.0–2.7 ) ( 60 ). The risk increases in women who smoked for a period of 16 years (OR: 3.23, 95% CI: 1.33, 7.69), and continue in recurrent smokers who consume more than 20 cigarettes a day ( OR: 2.57, 95% CI: 1.49 to 4.45 ) ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…A very important aspect of each specific oncological therapy is the implementation of the total planned course of treatment. The literature suggests that only 65-92% of patients receive the planned number of chemotherapy cycles [31]. This is often caused by the appearance of serious manifestations of ART [31].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that only 65-92% of patients receive the planned number of chemotherapy cycles [31]. This is often caused by the appearance of serious manifestations of ART [31]. It has been shown that patients from the control group received more than four cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…O entendimento da QVRS por parte do paciente e profissionais é fundamental para uma escolha conjunta das medidas terapêuticas que serão utilizadas, observando caso a caso e visando minimizar os efeitos do câncer e do tratamento. Pacientes que se submetem ao tratamento combinado de quimioterapia e radioterapia (CCRT) podem apresentar reações como: alterações hematológicas, náuseas, vômitos, diarreia, problemas pós-radiação precoce em trato gastrointestinal e bexiga 8 . Assim como estresse significativo, angústia existencial, depressão, ansiedade, insônia, tanto durante o tratamento, quanto na sobrevivência 9 .…”
Section: Introductionunclassified